The point symmetry group of a system of free second-order equations - Shapoval, N.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
It is proved that the complete point symmetry group of a system of free second-order ordinary differential equations is a projective general linear group acting in the space of independent and dependent variables.